Structure and optical properties of multi-phase structured amorphous silicon carbon nitride thin films deposited by plasma enhanced chemical vapour deposition / Mohd Azam Abdul Rahman - Mohd Azam , Abdul Rahman (2018)
The amorphous structured silicon carbide (a-SiC) thin films have been the focus of many studies due to its potential applications for high temperature devices operation in complement to conventional silicon microelectronics. Incorporation of nitrogen to silicon carbide thin films, has offered an effective route to produce hydrogenated amorphous silicon carbon nitride (a-SiCN:H) that combines the properties of silicon carbide, silicon nitride and carbon nitride. In current study, the variation in the structure, composition and optical properties of multi-phase structured hydrogenated amorphous silicon carbide (a-SiC:H) and a-SiCN:H thin films deposited by plasma-enhanced chemical vapour deposition (PECVD) with respect to nitrogen flow-rate is the focus in the first part of this work. Thereafter, the structure and optical properties of both multi-phase structured a-SiC:H deposited from the discharge of silane and methane as well as a-SiCN:H thin films deposited from the discharge of silane, methane and nitrogen with different flow-rate have been investigated in detail by using spectroscopy techniques. With respect to this, FTIR was used to probe the bonding structure in the film while Raman spectra of the films were used to understand the microstructure properties of the films related to the C-C bonds. Meanwhile, depth profiling analysis using Auger electron spectroscopy was used to probe the elemental composition of the films. Optical transmittance and reflectance spectra were utilized to determine the dispersion plot of refractive index of the films in the ultra-violet to the near infrared region. The optical energy gaps of the films were determined from the Tauc plot derived from the dispersion of absorption coefficient of the films calculated from the optical transmission spectra of the films. Optical constants, dispersion energy (ED) and single oscillator energy (E0) were determined from the dispersion of the refractive index plots using the Wemple-DiDomenico Model. The photoluminescence properties of the films were investigated and the origin of photoluminescence were accredited to the recombination within the tail states the hydrogenated amorphous carbon (a-C:H) phase in the films structure where the tail states are formed from sp2-C clusters in the film. The broad PL emission spectra were due to the overlapping of all the PL emission produced by the different phases in the film structure. Finally, comparative analysis was done on the structure and optical properties of the a-SiCN:H films after 30 days of deposition. Significant changes were observed in the chemical bonding properties of the films and the changes were different for the films deposited with and without nitrogen. The annealing of films at temperatures of 100 to 400 °C produced different effects on the structure and optical properties of the a-SiC:H and a-SiCN:H films. Decrease in the band gap energy value for the a-SiC:H film was due to evolution of hydrogen atoms from Si-CH3 bonds and breaking of weak Si-C bonds. However, the decrease in the band gap of the a-SiCN:H films was attributed to the decrease in C-N and Si-C-N bonds content in the film structure.